Canine insulinoma as a model for human malignant insulinoma research: Novel perspectives for translational clinical studies - Ylenia Capodanno (Elsevier, 2022)
Insulinomas are considered rare indolent neuroendocrine neoplasms in human medicine, however when metastases occur no curative treatment is available thus, novel therapies are needed. Recently advances have been made in unraveling the pathophysiology of malignant insulinoma still major challenges hinder the development of a functional model to study them. Canine malignant insulinoma have similar recurrence and a poor prognosis as human malignant insulinoma. Additionally, both human and canine patients share extensively the same environment, tend to develop insulinoma seemingly spontaneously with an etiological role for hormones, at a similar incidence and stage of lifespan, with metastasis commonly to liver and regional lymph nodes, which are unresponsive to current therapies. However, the occurrence of metastases in dogs is as high as 95% compared with only 5–16% in human studies. From a comparative oncology perspective, the shared features with human insulinoma but higher incidence of metastasis in canine insulinoma suggests the latter as a model for human malignant insulinomas. With the common purpose of increasing survival rates of human and veterinary patients, in this review we are going to compare and analyze clinical, pathological and molecular aspects of canine and human insulinomas to evaluate the suitability of the canine model for future translational clinical studies.